Ground-Based and Airborne Instrumentation for Astronomy VII 2018
DOI: 10.1117/12.2312069
|View full text |Cite
|
Sign up to set email alerts
|

The MICADO first light imager for ELT: its astrometric performance

Abstract: We report on our ongoing efforts to ensure that the MICADO NIR imager reaches differential absolute (often abbreviated: relative) astrometric performance limited by the SNR of typical observations. The exceptional 39m diameter collecting area in combination with a powerful multi-conjugate adaptive optics system (called MAORY) brings the nominal centroiding error, which scales as FWHM/SNR, down to a few 10 µas. Here we show that an exceptional effort is needed to provide a system which delivers adequate and cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…Modern astrometry has in large part been possibly by an increasing understanding of the instrumental distortions and the stability thereof. 2,[14][15][16][17][18] The distortions shown in the previous section are relatively small, compared to the typical geometric distortions expected from the optical design and telescope stability. Furhermore, the shape of these distortion patterns can be resolved by a third order polynomial, 18 resulting in an astrometric solution accurate to 8 µas, with a minor improvement when using a fifth order polynomial.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Modern astrometry has in large part been possibly by an increasing understanding of the instrumental distortions and the stability thereof. 2,[14][15][16][17][18] The distortions shown in the previous section are relatively small, compared to the typical geometric distortions expected from the optical design and telescope stability. Furhermore, the shape of these distortion patterns can be resolved by a third order polynomial, 18 resulting in an astrometric solution accurate to 8 µas, with a minor improvement when using a fifth order polynomial.…”
Section: Discussionmentioning
confidence: 87%
“…The instrument will be able to determine the relative distance between multiple point sources to an accuracy of 50 microarcseconds (µas). 2 The main challenge for reaching such performance lies in the understanding of the system stability -how image distortions change as the telescopes moves around, temperature variations occur and time passes. In this work we investigate the impact of wavefront errors on the geometric distortions, and subsequently on the astrometric accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…63 The requirements in regular imaging are 50 μas, with a goal of 20 μas. 68 This will be achieved thanks to a dedicated astrometric stability by design and built-in calibration strategy. However, high-precision astrometry in exoplanet imaging requires a dedicated strategy, as described in this paper using SPHERE as an example.…”
Section: Exoplanet Imaging With the Eltmentioning
confidence: 99%
“…As for this work, previous experience with the MCAO system at GeMS 17,47 has shown that the astrometric solution built within a single detector is systematically better and preferable to the global solution over the full detector array. These simulations do not include stability effects of the optomechanical tolerances that have a similar impact on the size of the correctable FoV (1 to 2 arc sec) as stated by Pott et al 16 The time-variant component of the distortions is represented here by the field rotation on top of the optics, which turns out to have a very similar amplitude and temporal behavior to the stability tolerances of the optics. The observation scenario shall be oriented toward the construction of local astrometric solutions over 2 arc sec 2 patches mosaicking larger fractions of the MICADO FoV or alternatively recalibrating the distortion pattern more frequently in the PA space when working on wider FoVs.…”
Section: This Distortion Study Concentrates On the Distorted Versus Distorted (Dd) Frames At Differentmentioning
confidence: 99%
“…For instruments such as MICADO 14 and IRIS, 15 the common figure of merit for the relative astrometry at single-and multi-epoch observations is 50 μas in the near-infrared (NIR) for sources ∼1 as apart. The origin and fundamental limits of achieving 50 μas-level astrometry with the ELT/MICADO was discussed by Pott et al 16 Generally, NIR refers to a wavelength range of 0.8 to 2.4 μm where typically higher AO performances (and boosted astrometry) are achieved at the red side of this range (H-K band). The ≃50 μas precision is intended as postfit, differential astrometry after having applied third to fifth or higher order polynomials that fit and remove the distortion pattern induced by the instrument to the image.…”
Section: Introductionmentioning
confidence: 99%